What's left of general jurisprudence? On law's ontology and content. (3rd April 2019) - Marmor, Andrei
ABSTRACT: The aim of this paper is to show that general jurisprudence is in no need of reinvention. The sentiment shared by many contemporary legal philosophers that theories about the nature of law have reached a dead end is challenged here by showing that the debates about the ontology of law and about the determinants of legal contents leave many interesting questions open for serious debate. The paper argues that traditional legal positivism is best seen as a theory about the ontological grounding of legal facts, and that a reductive account of this grounding can be provided with a more sophisticated account of the artefact nature of law, aided by some ideas derived from fictionalism. The paper also acknowledges that such a reductive ontology of law faces serious challenges, particularly from the view point of theories about determinants of legal contents. By explaining these challenges and pointing out how they may be met, the paper aims to show that some the age old debates about the nature or law are very much alive and worthy of serious philosophical inquiry.